Design of Energy Education Media For Solar and Wind Power Plants at Bomo Beach, Banyuwangi Regency - Adi Pratama Putra; Gatut Rubiono; Rezki Nalandari; Megandhi Gusti Wardhana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Bomo Beach, which is managed by community groups to become a tourist attraction, has the potential for renewable energy in the form of solar and wind energy. This potential can be harnessed and converted into electrical energy. This study aims to design energy education media for solar power plants and wind power plants at Bomo beach, Banyuwangi regency. The design is carried out in accordance with the natural management of tourist beach. The power plant designed is the integration of the solar power plant system (PLTS) and the wind power plant system (PLTB). Solar power plants use solar panels while PLTB uses horizontal shaft wind turbines and vertical shafts. The energy housing is made as a power store with a 12 volts battery. The design results show that the integration design of solar power plants and PLTB can be applied as an energy education media.